Diseño de un manual de funciones para la optimización del desempeño laboral en comercial Macías Cedeño - Zamora Sánchez, Fátima María (2025)
This research has been carried out following the guidelines for degree completion through comprehensive examination modality. It was identified that the commercial company Macias Cedeño, located in the province of Manabí, canton 24 de Mayo, faced difficulties in understanding different levels of management and lacked organization when executing operational-level tasks. This issue started due to the absence of an administrative tool to guide and direct employees in their tasks and roles according to their competencies and profiles. To address this, the design of a functions manual was proposed, detailing in a clear and structured manner the tasks and responsibilities of the personnel. This manual has been structured and supported by theoretical foundations from various authors, enabling a comprehensive understanding and a clear research approach. A qualitative approach was employed, allowing the delimitation of the current situation through an interview guide conducted with the company's legal representative, who highlighted a deficit in personnel operational management and the absence of the company’s mission and vision. A quantitative approach was also used, applying a survey to the employees. The number of respondents was eight people, representing the total staff. The results confirmed the existing problem. In this regard, a proposal was developed to optimize work performance, establish a strong organizational culture, and implement an efficient tool for assigning responsibilities and tasks in alignment with the company's objectives. The designed functions manual includes objectives, scope, legal framework, the company's organizational structure, mission and vision, corporate values, job descriptions, and specific functions of each role or position. Also, the functions manual will be introduced through a work meeting with the legal representative and employees to present the tool in all its phases, contributing to the proper execution and application of responsibilities and attributions efficiently aligned with the organization's proposed objectives. A control process will be carried out through a review of the results obtained after implementing the functions manual in the organization, using performance indicators to identify the level of compliance achieved.